P-438 Fertility outcomes in male cancer recipients of hematopoietic cell transplantation who stored their semen for fertility preservation. (30th June 2022) - Reschini, M; Cristina, M; Guarneri, C; Filippi, F; Somigliana, E; Boeri, L; Vigano', P
Abstract: Study question: What are the prevalence estimates of post-hematopoietic cell transplantation (HCT) natural conceptions or after ART using stored semen? Summary answer: Natural live birth rate following HCT can be estimated at 9% (95%CI:4-22%) but can be increased to 58% (95%CI:43-72%) with the use of frozen semen. What is known already: With the improvements and expanding indications of HCT, the number of adult male cancer survivors who received HCT is increasing. These men face the risk of treatment-induced infertility and are generally recommended to store their semen prior to embark in HCT. However, information on long term usage and on effectiveness of frozen sperm samples in this specific population is not well defined. Study design, size, duration: All male cancer recipients of autologous or allogeneic transplantation who cryopreserved semen between 1987 and 2016 in the biobank of the Assisted Reproductive Technology Unit of the Fondazione IRCCS Cà Granda Ospedale Maggiore Policlinico in Milan were considered. Information was obtained from patients' charts or through active investigation. The main studied topics included results from semen analyses, attempt to parenthood, use of stored spermatozoa and both natural and Assisted Reproductive Technique (ART) mediated conceptions. Participants/materials, setting, methods: The study is restricted to men who met the following eligibility criteria: i) semen cryopreserved for fertility preservation between 1987 and 2016; ii) post-banking follow-up documenting HCT iii) survival of at least 5 years from HCT. Main results and the role of chance: One-hundred and two HCT survivors were selected. The median [IQR] age at sperm banking was 29 [23-34]. About half of subjects had autologous HCT (n = 50), the remaining 52 received allogenic HCT. Lymphomas were the most frequent indications. The median spermatozoa concentration at the time storage was 39 [7-85] millions/ml. Fifty-four (53%) men performed a post-treatment sperm analysis and azoospermia was documented in 45 of them (83%, 95%CI: 71-91%). The remaining nine showed viable spermatozoa, of whom six had severe oligospermia (concentration <1 million/mL). The other three had semen concentration >5 Millions/ml, compatible with a natural conception. Overall, based on semen analyses, one could infer the necessity to use ART in 51 out of 54 subjects, corresponding to 94% (95%CI: 85-98%). Forty-three of the 102 included men (42%) sought childbearing. Four had a natural live birth (9%, 95%CI: 4-22%). Thirty-three used their cryopreserved sperm samples, corresponding to 32% (95%CI: 24-42%) of the whole cohort. Twenty-one of these 33 men had at least one live birth (64%, 95%CI: 47-78%). Finally, six men seeking pregnancy and who did not conceive have not used their frozen semen. Overall, 25 out of 43 men interested in fatherhood had a live birth (58%, 95%CI: 43-72%). Limitations, reasons for caution: Limitation of our study is missing detailed information on status of illness and comorbidities (in particular the frequency of Graft-versus host disease) and lack precise information on the myeloablative regimen used. Furthermore, our sample size is not very large and therefore the 95%CI of the reported proportions are wide. Wider implications of the findings: Autologous or allogeneic HCT induces infertility in a very high percentage of patients. These findings support the need to prioritize sperm preservation before HCT also in cancer patients who are not candidate for HCT at first instance but who may need this treatment for failure of first line treatments. Trial registration number: not applicable